2001
DOI: 10.1002/bem.37
|View full text |Cite
|
Sign up to set email alerts
|

Large granular lymphocytic (LGL) leukemia in rats exposed to intermittent 60 Hz magnetic fields

Abstract: An animal model for large granular lymphocytic (LGL) leukemia in male Fischer 344 rats was utilized to determine whether magnetic field exposure can be shown to influence the progression of leukemia. We previously reported that exposure to continuous 60 Hz, 1 mT magnetic fields did not significantly alter the clinical progression of LGL leukemia in young male rats following injection of spleen cells from donor leukemic rats. Results presented here extend those studies with the following objectives: (a) to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…No overall effects of 60 Hz and 1 mT MF on splenomegaly or survival were found in the exposed Fischer/344 rats. In addition, no significant and/or consistent differences were detected in the hematological parameters between the exposed and control rats [242]. MF exposure for 14 weeks to 6.45 µT did not appear to be a strong co-tumorigenic agent in Sprague-Dawley female rats mammary, lung, and skin models [243].…”
Section: Studies On Ratmentioning
confidence: 85%
“…No overall effects of 60 Hz and 1 mT MF on splenomegaly or survival were found in the exposed Fischer/344 rats. In addition, no significant and/or consistent differences were detected in the hematological parameters between the exposed and control rats [242]. MF exposure for 14 weeks to 6.45 µT did not appear to be a strong co-tumorigenic agent in Sprague-Dawley female rats mammary, lung, and skin models [243].…”
Section: Studies On Ratmentioning
confidence: 85%
“…Only in male rats was the incidence of thyroid gland C-cell neoplasm increased when they were exposed to 2 or 200 T (28), whereas in the study of McCormick et al (39) lymphoma development in female mice exposed to 1 mT was even decreased. Fischer 344 rats were also used to study whether magnetic-field exposure (60 Hz) can influence the progression of leukemia after intraperitoneal injection with leukemic spleen cells (40). No influence of the exposure could be detected on body weight, survival, splenomegaly or leukemia incidence rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous review (1) we discussed experiments of Dieter and colleagues (100) and suggested that their report of enhancement effects may not be definitive. More (79)(80)(81)(82)101) appear to be well done, the significance of the results with respect to whether MFs have any leukemogenic potential is uncertain. Below, we review the experiments conducted by this group.…”
Section: Resultsmentioning
confidence: 99%